The Study of High School Studentâs Scientific Attitudes on Learning Heat and Temperature with Cooperative Inquiry Labs Model - Gani, Abdul; Safitri, Rini; *, Habibati; Saminan, Nurul Fajri (Sebelas Maret University, 2016)
Scientific attitude is an approach to investigations that benefits from certain traits namely; curiosity or inquisitiveness, objectivity, open-mindedness, perseverance, humility, ability to accept failure, and skepticism. Scientific attitude is one of benchmarks for the success of science learning process especially the level of understanding of the concept of physics. This study aims to analyse the studentsâ scientific attitude on learning heat and temperature with Cooperative Inquiry Labs (CIL) model at SMAN 6 Banda Aceh. This is a quasi experimental research with the class subject of X-MIA1 as a control class and X-MIA2 as an experimental class. Data collection technique used was by giving a questionnaire containing seven kinds of scientific attitude indicators to each student. The questionnaire in this study used a Likert scale with four categories of responses. Data tabulation was done by testing the average difference of two independent samples, indicated that tcount (10.94) > ttable (2.01) at the significant level of 5%, which means that there are significant differences in outcomes between the experimental and control classes. The results of questionnaire analysis showed that in the control class, there were four scientific attitude indicators which had high category, and the three other indicators were in medium category, whereas in the experimental class, there were five indicators with high category and two indicators with medium category. Based on the data of the analysis result of t test showed the scientific attitude of the students in both classes were tcount = 2.09 which was bigger than ttable = 2.01, and because of the significance of <0.05, it can be said that there was a significant difference after the learning process with CIL model.